A generic method for servo tuning based on dynamic modeling and task description. (September 2018) - Paccot, Flavien; Chanal, Helene
Abstract: In robotics or machining, task quality is strongly linked to servo tuning. Indeed, geometrical and dynamic behavior of the mechanical structure could be degraded when a coarse tuning is achieved. Several P/PI or PID tuning methods can be used but generally uncorrelated with industrial context or mechanical considerations. In this paper, we propose a generic tuning method based on dynamic modeling of the mechanical structure and model parameters experimental identification. Therefore, the proposed tuning is adapted to the real dynamic behavior of the mechanical structure under task load while being sufficiently simple to be implemented in an industrial context. The method is illustrated on a vertical axis. Highlights: This paper deals with a new tuning method adapted to robots and machines with regards to the task and structure specificities. This tuning method is validated experimentally on a vertical axis. The tuning method is based on the mechanical structure dynamic modeling. The dynamic parameters are identified under task solicitations to ensure reliability with the real behavior of the machine.